SIKAP SISWA DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR DI KABUPATEN LAMANDAU - Arvi, Arvi Riwahyudin (Pascasarjna Universitas Negeri Jakarta, 2015)
Abstract: The purpose of this study was to determine the direct influence student attitudes and interests of student learning to the learning outcomes Elementary School fifth grade science students in District Menthobi Raya Regency Lamandau. This study uses a quantitative approach with survey method with a causal approach. Sampling study amounted to 40 respondents. Withdrawal of the number of samples using Cluster Random Sampling (Sampling Area). The findings of this research are: 1) The attitude of the students positive direct effect on learning outcomes IPA elementary school students in District Menthobi Raya Regency Lamandau. That is the positive attitude of students in the study will lead to good learning outcomes, 2) Interest in learning a direct positive effect on learning outcomes Elementary School fifth grade science students in District Menthobi Raya Regency Lamandau. This means that there is interest in learning on students will lead to good learning outcomes, 3) direct effect positive student attitude toward interest in learning science elementary school students in District Menthobi Raya Regency Lamandau. Keywords: Student Attitude, Interest In Learning, Learning Outcomes. Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh langsung Sikap siswa dan Minat belajar siswa terhadap hasil belajar IPA siswa kelas V SD di Kecamatan Menthobi Raya Kabupaten Lamandau. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey dengan pendekatan kausal. Pengambilan sampel penelitian berjumlah 40 responden. Penarikan jumlah sampel menggunakan Cluster Random Sampling (Area Sampling). Temuan yang didapat dari penelitian ini adalah: 1) Sikap siswa berpengaruh langsung positif terhadap hasil belajar IPA siswa SD di Kecamatan Menthobi Raya Kabupaten Lamandau. Artinya sikap siswa yang positif dalam belajar akan menyebabkan hasil belajar yang baik, 2) Minat belajar berpengaruh langsung positif terhadap hasil belajar IPA siswa kelas V SD di Kecamatan Menthobi Raya Kabupaten Lamandau. Artinya minat belajar yang ada pada diri siswa akan menyebabkan hasil belajar yang baik, 3) Sikap siswa berpengaruh langsung positif terhadap minat belajar IPA siswa SD di Kecamatan Menthobi Raya Kabupaten Lamandau. Kata kunci: Sikap siswa, Minat belajar, Hasil belajar.